Odpowiedź :
Odpowiedź:
6)
a) x/5 + 8 = 20 - 8
x/5 = 12 | * 5
x = 60
------------------
b) 3 + x/3 = 4
x/3 = 4 - 3
x/3 = 1 | * 3
x = 3
7)
a) 3(x - 5) = 9
3x -15 = 9
3x = 9 + 15
3x = 24 | : 3
x = 8
-------------------
b) 4(x + 1) = -8
4x + 4 = -8
4x = -8 -4
4x = -12 | : 4
x = -3
-------------------
8)
a) 2x + 5 + x - 2 = 12
3x = 12 - 5 + 2
3x = 9 | : 3
x = 3
-------------------
b) -3x - 1 + 5x + 7 = 0
2x = 0 + 1 - 7
2x = -6 | : 2
x = -3
-------------------
c) 4x + 7 - x + 2 = 9
4x + 9 - x = 9
3x + 9 = 9 | - 9
3x = 0
3x/3 = 0/3
x = 0
----------------------
(9?)
b) 3x - 4 = 5x
-2x = 4 | : (-2)
x = -2
--------------------------
d) -2x = 7x + 18
-9x = 18 | : (-9)
x = -2
Szczegółowe wyjaśnienie:
Odpowiedź:
6.
a) [tex]\frac{x}{5}[/tex] + 8 = 20 / -8
[tex]\frac{x}{5}[/tex] = 12 / *5
x = 60
b) 3 + [tex]\frac{x}{3}[/tex] =4 /-3
[tex]\frac{x}{3}[/tex] = 1 /*3
x = 3
7.
a) 3(x-5) = 9
3x - 15 = 9 /+15
3x = 24 /:3
x = 8
b) 4(x+1) = -8
4x + 4 = -8 /-4
4x = 12 /:4
x = 3
8.
a) 2x + 5 + x - 2 = 12
3x + 3 = 12 /-2
3x = 9 /:3
x = 3
b) -3x - 1 + 5x + 7 = 0
2x + 6 = 0 /-6
2x = -6 /:2
x = -3
c) 4x + 7 - x + 2 = 9
3x + 9 = 9 /-9
3x = 0 /:3
x = 0